2003
DOI: 10.1238/physica.regular.067a00525
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Molecular Quadrupole Moment of Boron Trichloride by Microwave Spectroscopy

Abstract: The foreign-gas broadening parameter for fluoroform molecules interacting with nonpolar BCl3 molecule as perturber has been measured and the collision cross section has been determined. The results are pressure broadening coefficient Cw = (43 ± 1) [kHz/Pa] for J = 1 ← 0 rotational transition of CHF3 molecule in mixture with BCl3 gas, and collision cross section σexp = 294.0 [Å2]. Experimental linewidth parameter is interpreted using Anderson–Tsao–Curnutte as well as Murphy–Boggs theories for the mixed- inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…12 However, Ritchie has raised objections to the assumptions made in that work, 13 arguing that the absorber-perturber collision cross section is not proportional to ͑⌰ 2 M͒ 1/3 where M is the reduced mass of the absorber-perturber collision pair, and that the observed spectral broadening cannot be interpreted solely on the basis of dipole-quadrupole interactions. The first assumption relied on old ⌰ values, for which Ritchie has shown that, when more recent and reliable values are used, the assumed proportionality is qualitatively and quantitatively incorrect.…”
Section: B the Quadrupole Momentmentioning
confidence: 97%
See 4 more Smart Citations
“…12 However, Ritchie has raised objections to the assumptions made in that work, 13 arguing that the absorber-perturber collision cross section is not proportional to ͑⌰ 2 M͒ 1/3 where M is the reduced mass of the absorber-perturber collision pair, and that the observed spectral broadening cannot be interpreted solely on the basis of dipole-quadrupole interactions. The first assumption relied on old ⌰ values, for which Ritchie has shown that, when more recent and reliable values are used, the assumed proportionality is qualitatively and quantitatively incorrect.…”
Section: B the Quadrupole Momentmentioning
confidence: 97%
“…u. 12 However, questions regarding this work have been raised, 13 highlighting deficiencies in the experimental technique as well as limitations in the approximations made by Gierszal et al The experimentally derived value assumed both a vanishing octupole moment of BCl 3 and a vanishing quadrupole moment of CHF 3 , neither of which are valid assumptions. 23 Clearly, the definitive value of this property has yet to be established.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations